Cyber Legal Responsibility for Personal Data Leaks from the Perspective of Substantive Justice in Indonesia - Dede Taufik, Hariang; Apandi, Haerul; Paskaries, Rudolf; Aritonang, Hariyanto; Haruman, Andi; Pranadita, Nugraha (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Digital transformation has increased the use of personal data as a strategic asset in various sectors, but it has also given rise to the risk of data leaks that cause material and immaterial losses to society. This study aims to analyse cyber legal liability for personal data leaks in Indonesia using a substantive justice perspective. The method used is descriptive qualitative through a literature study of regulations, legal doctrines, and data protection practices to obtain a comprehensive understanding of legal responsibility in the digital ecosystem. The results of the study show that cyber legal responsibility still faces challenges of cross-border jurisdiction, weak implementation of the responsibility of digital corporations as legal subjects, and suboptimal restoration of victims' rights. A damage-based jurisdiction approach is needed to reach global digital actors, while strengthening corporate accountability is key to preventing avoidance of responsibility. From a substantive justice perspective, the legal system needs to be oriented towards the effective restoration of victims' rights through compensation, ongoing protection, and system improvements. This study emphasises that strengthening an adaptive, accountable, and victim-oriented cyber legal framework is an important prerequisite for realising fair personal data protection and increasing public trust.